MORAL VALUES AND ETHICS IN A CHILDREN’S PICTURE BOOK “OF THEE IS SING: A LETTER TO MY DAUGHTERS” BY BARACK OBAMA - Feti Kaniasari; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of this study was to analyze: 1) Moral values in a children’s picture book "Of Thee I Sing: A Letter to My Daughters" by Barack Obama. 2) Ethics in a children’s picture book "Of Thee I Sing: A Letter to My Daughters" by Barack Obama. The method used in this research is descriptive-qualitative which aims to describe moral values and ethics in the children picture book Of Thee I Sing: A Letter to My Daughters. The result of the analysis: 1) In moral values, self-confidence get the highest percentage of 45.65 %, bravery 19.56 %, strong belief 15.22 %, peace loving 10.87%, love and affection 8.69%. 2) While ethics, justice and beneficence get the highest percentage of 25 %, rights 22.5 %, utilitarianism 10%, and respect for autonomy 17.5%.Keywords: moral values, ethics, children, picture book.